Ocena efektów pracy w kosztowych ośrodkach odpowiedzialności - Parkitna, Agnieszka (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The paper introduces the problem of estimation of works effects. The author presents functions of the estimation, then discusses the estimation of individual works effects as well as of joint works effects in cost responsibility centres. As a result, the author proposes the criteria and measures of works effects estimation in cost responsibility centres. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 350-366